Multidimensional factors contributing to the dynamics of ethnic conflict in Ethiopia - Keneni Jibat; Yonas Aday Adeto; Taddesse Berisso Galchu (Cogent Social Sciences)
In Ethiopia, ethnic federalism was implemented in the 1990s with the intention of redressing past marginalization, in which certain groups were excluded from political participation, economic prospects, and cultural acknowledgement. Here Ethnic conflict refers to a form of conflict in which the objectives of at least one party are defined in ethnic terms. However, it’s essential to note that the conflict itself is usually not about ethnic differences per se. Instead, it revolves around political, economic, social, cultural, or territorial matters. There are conflicts over political and territorial authority among Ethiopian ethnic groups, despite the fact that these conflicts are the result of disputed histories and feelings of marginalization. This study aims to investigate the dynamics of political tensions among Ethiopian regions. A qualitative research methodology is used. Both primary and secondary data sources were used. The findings show that Ethiopia’s 1991 transition to ethnic federalism was a drastic attempt to balance the country’s ethnic diversity within its political system. Nevertheless, this system has also been criticized for escalating ethnic conflicts and fostering a politicized environment where ethnicity plays a big role in resource distribution and government.